Lifestyle, death-style, and religious arenas - Douglas J. Davies (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
In this paper I want to extend the debate to embrace the theme of death as a theme lying at the centre of most of the great world religious traditions and their local presence in funerary rites. Approaching death in this way provides a significant medium of expressing the core values of a society and, therefore, of expressing similarities and differences between societies. This paper does no more than raise some possible areas of future discussion on the global-local comparisons of types of death as arenas of cultural expression of human existence. As argued at the end of this paper, cultural wisdom is, perhaps, a concept that can serve well in our ongoing discussions of the interface between the global and local dynamics of lifestyle and death-style, where death offers us a window upon our great and little worlds.